Pengaruh Komitmen Profesional, Sosialisasi Antisipaotf, Status Pelanggar, dan Retaliasi terhadap Intensi Whistleblowing Mahasiswa Akuntansi - Ni Luh Yuli Candra Dewi; Edy Sujana (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2023)
Abstract This studies was carried out to decide the effect of professional commitment, anticipatory socialization, status of wrongdoer, and retaliation at the whistleblowing intentions of accounting students. This have a look at uses a descriptive quantitative method as a research technique with primary records sources obtained from the results of distributing on line questionnaires using Google shape. The studies places are in five universities in Bali Province, along with 2 PTN and 3 PTS with a complete pattern of 214 respondents who were taken with the aid of purposive sampling approach. The consequences of the study provide evidence that the variables of professional commitment and anticipatory socialization have a positive and good sized effect at the whistleblowing intentions of accounting college students. The retaliation variable has a poor and sizable effect on the whistleblowing intentions of accounting students. Meanwhile, the status of wrongdoer variable has a bad and insignificant impact on the whistleblowing goal of accounting college students. Keywords: Professional Commitment, Anticipatory Socialization, Status of Wrongdoer, Retaliation, Whistleblowing Intention